Ag/ZnO core–shell NPs boost photosynthesis and growth rate in wheat seedlings under simulated full sun spectrum - Shahnoush Nayeri; Mahboubeh Dolatyari; Neda Mouladoost; Saeed Nayeri; Armin Zarghami; Hamit Mirtagioglu; Ali Rostami (Scientific Reports, 2023)
Abstract Breeding programs rely on light wavelength, intensity, and photoperiod for rapid success. In this study, we investigated the ability of Ag/ZnO nanoparticles (NPs) to improve the photosynthesis and growth of wheat under simulated full solar spectrum conditions. The world population is increasing rapidly, it is necessary to increase the number of crops in order to ensure the world’s food security. Conventional breeding is time-consuming and expensive, so new techniques such as rapid breeding are needed. Rapid breeding shows promise in increasing crop yields by controlling photoperiod and environmental factors in growth regulators. However, achieving optimum growth and photosynthesis rates is still a challenge. Here, we used various methods to evaluate the effects of Ag/ZnO NPs on rice seeds. Using bioinformatics simulations, we evaluated the light-harvesting efficiency of chlorophyll a in the presence of Ag/ZnO NPs. Chemically synthesized Ag/ZnO nanoparticles were applied to rice grains at different concentrations (0–50 mg/L) and subjected to a 12-h preparation time. Evaluation of seed germination rate and growth response in different light conditions using a Light Emitting Diode (LED) growth chamber that simulates a rapid growth system. The analysis showed that the surface plasmon resonance of Ag/ZnO NPs increased 38-fold, resulting in a 160-fold increase in the light absorption capacity of chlorophyll. These estimates are supported by experimental results showing an 18% increase in the yield of rice seeds treated with 15 mg/L Ag/ZnO NPs. More importantly, the treated crops showed a 2.5-fold increase in growth and a 1.4-fold increase in chlorophyll content under the simulated full sun spectrum (4500 lx) and a 16-h light/8-h dark photoperiod. More importantly, these effects are achieved without oxidative or lipid peroxidative damage. Our findings offer a good idea to increase crop growth by improving photosynthesis using Ag/ZnO nanoparticle mixture. To develop this approach, future research should go towards optimizing nanoparticles, investigating the long-term effects, and exploring the applicability of this process in many products. The inclusion of Ag/ZnO NPs in rapid breeding programs has the potential to transform crops by reducing production and increasing agricultural productivity.